2004
DOI: 10.1080/02640410400005933
|View full text |Cite
|
Sign up to set email alerts
|

Altitude and endurance training

Abstract: The benefits of living and training at altitude (HiHi) for an improved altitude performance of athletes are clear, but controlled studies for an improved sea-level performance are controversial. The reasons for not having a positive effect of HiHi include: (1) the acclimatization effect may have been insufficient for elite athletes to stimulate an increase in red cell mass/haemoglobin mass because of too low an altitude (< 2000-2200 m) and/or too short an altitude training period (<3-4 weeks); (2) the training… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
115
3
6

Year Published

2006
2006
2019
2019

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 147 publications
(137 citation statements)
references
References 121 publications
10
115
3
6
Order By: Relevance
“…In addition, arrhythmia is one of the physiological responses to hypoxia exposure, caused by ventilator and circulatory responses that are accompanied by an increase in the sympathetic activity and local vasoregulatory effects. Therefore, these are undoubtedly key mechanisms improving oxygen delivery to tissues [1,35]. The increase in the amount of NeuroPs in urine is also evidence that the hard work involved in elite training results in OS in tissues where DHA is present -like muscle, as well as adipose tissue, rectal epithelium, liver and spleen, heart and cheek, red blood cells, and sperm.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, arrhythmia is one of the physiological responses to hypoxia exposure, caused by ventilator and circulatory responses that are accompanied by an increase in the sympathetic activity and local vasoregulatory effects. Therefore, these are undoubtedly key mechanisms improving oxygen delivery to tissues [1,35]. The increase in the amount of NeuroPs in urine is also evidence that the hard work involved in elite training results in OS in tissues where DHA is present -like muscle, as well as adipose tissue, rectal epithelium, liver and spleen, heart and cheek, red blood cells, and sperm.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that 10-epi-10-F 4t -NeuroP and 10-F 4t -NeuroP may be potential biomarkers of lipid peroxidation physical exercise under hypoxia (low levels of oxygen) at moderate altitude (2320 m altitude). The effects of hypoxia in the brain may influence the training intensity and/or the physiological responses during training at altitude [1]. In cerebral cortex of newborn pigs, an increase in the levels of F 4 -NeuroP and other OS markers, after hypoxia and resuscitation with supplementary oxygen (reoxygenation), was detected [33].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Using this method, athletes live at moderate altitude (2,500 m) and train at low altitude (1,250 m) which allows athletes to obtain the benefits of altitude acclimatization and continue to train at high intensities, resulting in improvements of aerobic capacity (VO 2 max), ventilatory threshold (VT) and performance at sea level (Chapman et al, 1998;Levine and Stray-Gundersen, 1997;Levine et al, 1991;Mattila and Rusko, 1996;Roberts et al, 2003;Rusko et al, 1999). It has been suggested that in order to obtain the benefits of acclimatized altitude training the athlete must spend at least 12 hours a day for at least 3 weeks at an altitude of 2100-2500m (Rusko et al, 2004). This exposure to hypoxic conditions stimulates the kidneys to produce erythropoietin (EPO), which increases red blood cell (RBC) production (Paula and Niebauer, 2012).…”
Section: Introductionmentioning
confidence: 99%